A cold rolled dual phase steel and a method for producing the same
Patent Information
- Application Number
- CN202611219738.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-27
AI Technical Summary
然而,上述研究未涉及折弯性能的改善,且添加合金元素钼会造成制造成本增加
本申请实施例提供了一种冷轧双相钢及其制备方法,以质量分数计,所述冷轧双相钢的化学成分为:C:0.07%~0.12%,Si:0%~0.40%,Mn:1.80%~2.30%,Al:0.02%~0.06%,Cr:0.30%~0.60%,Nb:0.01%~0.04%,Ti:0.01%~0.04%,P:0%~0.01%,S:0%~0.005%,其余为Fe及不可避免的杂质;所述冷轧双相钢的显微组织包括细小均匀的铁素体、弥散呈岛状分布的马氏体、贝氏体和残余奥氏体;所述冷轧双相钢的表面脱碳层厚度为5μm~30μm。从化学成分来看,通过采用C、Mn、Cr、Nb和Ti等元素组合,不添加高成本的Mo元素,同时将Al的质量分数控制在较低范围,在降低制造成本的同时为后续组织调控奠定了成分基础。特别是Nb和Ti的微合金化作用,能够细化晶粒并促进马氏体弥散分布,从而改善冷轧双相钢的扩孔性能。从显微组织来看,冷轧双相钢的组织由较软的铁素体基底和硬质的马氏体增强相组成。通过获得细小均匀的铁素体基体以及弥散呈岛状分布的马氏体,有效避免了因组织分布不均匀导致的局部应变集中。这种组织设计有利于减轻折弯过程中裂纹的萌生倾向,同时岛状马氏体的均匀分布有助于应变的均匀分配,从而兼顾了冷轧双相钢扩孔性能的提升。此外,贝氏体和残余奥氏体的存在进一步优化了冷轧双相钢的塑性变形能力。从表面脱碳层厚度来看,通过连续退火炉内分段加湿工艺,在冷轧双相钢表面形成厚度可控的脱碳层,增加了表层铁素体体积分数。脱碳层构建有效提升了冷轧双相钢表层的延伸率,而表层延伸率的改善直接有利于折弯过程中裂纹的萌生与扩展抑制,从而显著提升折弯性能。这种表面处理从冷轧双相钢表层入手,在不影响内部组织均匀性的前提下,实现了折弯性能的提升。
Smart Images

Figure CN122979772A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of iron and steel smelting technology, and in particular to a cold-rolled duplex steel and its preparation method. Background Technology
[0002] High-strength cold-rolled dual-phase steel consists of a relatively soft ferrite matrix and a hard martensitic reinforcing phase. This two-phase microstructure endows cold-rolled dual-phase steel with a wide range of tunable mechanical properties and a good balance between strength and plasticity. Cold-rolled dual-phase steel exhibits a low yield strength ratio, a high work hardening rate, and good elongation. Simultaneously, the total alloy element content generally does not exceed 4%, and this low alloy content results in lower production costs, good weldability, and excellent coating performance. With its high strength, excellent formability, and strong impact energy absorption capacity, this cold-rolled dual-phase steel has been widely used in the automotive industry, becoming an important material for automotive lightweighting and gradually developing into one of the preferred steel grades for automobiles.
[0003] Currently, some technical problems still exist in the actual production and application of cold-rolled duplex steel. Uneven microstructure distribution easily leads to poor bending performance, a problem particularly prominent in thick-gauge cold-rolled duplex steel. Simultaneously, insufficient expansion ratio in cold-rolled duplex steel easily results in defects such as cracking during flanging and expansion forming. Research shows that there is often a contradictory relationship between the bending performance and expansion performance of cold-rolled duplex steel: improving bending performance usually requires increasing the elongation of the cold-rolled duplex steel, but when reducing the yield strength ratio to increase elongation, the hardness difference between ferrite and martensite increases, which is detrimental to improving the expansion ratio.
[0004] Existing research primarily focuses on improving the hole-expanding performance of cold-rolled duplex steel. Studies have shown that dispersing martensite into island-like patterns promotes uniform strain distribution, thereby reducing localized high-strain strengthening. Furthermore, adding microalloying elements to refine the microstructure and increasing the yield strength ratio of ultra-high-strength cold-rolled duplex steel both contribute to improved hole-expanding performance. However, these studies do not address improvements in bending performance, and the addition of molybdenum increases manufacturing costs. Additionally, existing technologies achieve good bending performance through controlled annealing processes, but this method involves galvanizing and does not address how to improve the bending performance of continuously annealed duplex steel, nor does it explain the control level of the hole-expanding rate in this approach. Moreover, the high cost of molybdenum in this approach increases production and procurement costs for both manufacturers and users. Summary of the Invention
[0005] This application provides a cold-rolled duplex steel and its preparation method to solve the following technical problem: how to simultaneously take into account the bending performance and hole expansion performance of cold-rolled duplex steel. In a first aspect, embodiments of this application provide a cold-rolled dual-phase steel, wherein the chemical composition of the cold-rolled dual-phase steel, by mass fraction, is: C: 0.07%~0.12%, Si: 0%~0.40%, Mn: 1.80%~2.30%, Al: 0.02%~0.06%, Cr: 0.30%~0.60%, Nb: 0.01%~0.04%, Ti: 0.01%~0.04%, P: 0%~0.01%, S: 0%~0.005%, with the remainder being Fe and unavoidable impurities; The microstructure of the cold-rolled dual-phase steel includes fine and uniform ferrite, diffusely distributed martensite, bainite, and retained austenite. The thickness of the decarburized layer on the surface of the cold-rolled duplex steel is 5μm~30μm.
[0006] Optionally, the volume fraction of ferrite is 43% to 55%, and the volume fraction of martensite is 35% to 55%.
[0007] Optionally, the cold-rolled duplex steel meets the following properties: yield strength of 435MPa~535MPa, tensile strength of 780MPa~900MPa, and longitudinal elongation A. 80 ≥19%, with an expansion rate of 35%~45%, and no cracking when bending at 90° laterally with a bending mandrel radius of 0.5mm.
[0008] Secondly, embodiments of this application provide a method for preparing the cold-rolled dual-phase steel described in the first aspect, the method comprising: Molten steel with the following chemical composition is subjected to ladle refining and vacuum circulation degassing treatment in sequence. The molten steel after vacuum circulation degassing treatment is then continuously cast to obtain a slab with the following composition: C: 0.07%~0.12%, Si: 0%~0.40%, Mn: 1.80%~2.30%, Al: 0.02%~0.06%, Cr: 0.30%~0.60%, Nb: 0.01%~0.04%, Ti: 0.01%~0.04%, P: 0%~0.01%, S: 0%~0.005%, with the remainder being Fe and unavoidable impurities. The slab is sequentially heated, rough-rolled, finish-rolled, and coiled to obtain a hot-rolled coil. The hot-rolled coil is sequentially pickled and cold-rolled in multiple passes to obtain a cold-hardened coil. The cold-rolled coil is subjected to continuous annealing and finishing to obtain cold-rolled dual-phase steel.
[0009] Optionally, the heating temperature is 1200℃~1280℃, the heating time in the furnace is 180min~260min, and the heating soaking time is ≥35min.
[0010] Optionally, the finishing rolling temperature is ≥880℃.
[0011] Optionally, the winding temperature is 500℃~600℃.
[0012] Optionally, the total reduction rate of the multi-pass cold rolling is 45% to 70%.
[0013] Optionally, the continuous annealing speed is 90 m / min to 180 m / min.
[0014] Optionally, the continuous annealing includes a heating stage, a heating stage, a soaking stage, a slow cooling stage, a rapid cooling stage, an aging stage, and an aging stage. The temperature of the heating section is 400℃~550℃, and the heating rate of the heating section is 0.7℃ / s~2.4℃ / s; The temperature of the second heating section is 780℃~840℃, and the heating rate of the second heating section is 1.5℃ / s~5.4℃ / s; The temperature of the heat spreader is 780℃~840℃; The temperature of the slow cooling section is 600℃~680℃; The temperature of the rapid cooling section is 270℃~350℃, and the rate of the rapid cooling section is 20℃ / s~60℃ / s; The temperature for the first aging stage is 270℃~350℃; The temperature of the second aging stage is 300℃~400℃, and the temperature of the second aging stage is 20℃~50℃ higher than the temperature of the first aging stage.
[0015] Optionally, the cold-hardened roll is subjected to segmented humidification during the continuous annealing process, and the flow rate of the segmented humidification process is 5 kg / h to 20 kg / h; the segmented humidification process is carried out in the first heating stage and / or the second heating stage temperature zone.
[0016] The technical solutions provided in this application have the following advantages compared with the prior art: This application provides a cold-rolled duplex steel and its preparation method. The chemical composition of the cold-rolled duplex steel, by mass fraction, is: C: 0.07%~0.12%, Si: 0%~0.40%, Mn: 1.80%~2.30%, Al: 0.02%~0.06%, Cr: 0.30%~0.60%, Nb: 0.01%~0.04%, Ti: 0.01%~0.04%, P: 0%~0.01%, S: 0%~0.005%, with the remainder being Fe and unavoidable impurities. The microstructure of the cold-rolled duplex steel includes fine and uniform ferrite, diffusely distributed martensite, bainite, and retained austenite. The thickness of the decarburized layer on the surface of the cold-rolled duplex steel is 5μm~30μm. From a chemical composition perspective, by employing a combination of elements such as C, Mn, Cr, Nb, and Ti, without adding the high-cost element Mo, and controlling the Al mass fraction within a low range, the manufacturing cost is reduced while laying the compositional foundation for subsequent microstructure control. In particular, the microalloying effect of Nb and Ti refines the grains and promotes the dispersed distribution of martensite, thereby improving the hole-expanding performance of cold-rolled duplex steel. From a microstructure perspective, the cold-rolled duplex steel consists of a relatively soft ferrite matrix and a hard martensite reinforcing phase. By obtaining a fine and uniform ferrite matrix and dispersed island-like martensite, local strain concentration caused by uneven microstructure distribution is effectively avoided. This microstructure design helps reduce the tendency for crack initiation during bending, while the uniform distribution of island-like martensite contributes to the uniform distribution of strain, thus improving the hole-expanding performance of cold-rolled duplex steel. Furthermore, the presence of bainite and retained austenite further optimizes the plastic deformation capacity of cold-rolled duplex steel. From the perspective of surface decarburization layer thickness, a controllable decarburization layer is formed on the surface of cold-rolled duplex steel through a segmented humidification process in a continuous annealing furnace, increasing the volume fraction of surface ferrite. The construction of this decarburization layer effectively improves the elongation of the surface layer of the cold-rolled duplex steel. This improved elongation directly benefits the initiation and propagation of cracks during bending, thus significantly improving bending performance. This surface treatment, starting from the surface layer of cold-rolled duplex steel, achieves improved bending performance without affecting the uniformity of the internal microstructure.
[0017] In summary, by combining low-cost alloy composition design, dispersion island martensite microstructure control, and surface decarburization layer construction, this approach addresses both the bulk and surface dimensions of cold-rolled dual-phase steel. It improves elongation and bending performance through the surface decarburization layer and enhances hole-expanding performance through microstructure uniformity and hardness difference control. This effectively solves the technical challenge of simultaneously achieving both bending and hole-expanding performance in cold-rolled dual-phase steel. Attached Figure Description
[0018] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.
[0019] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, those skilled in the art can obtain other drawings based on these drawings without any creative effort.
[0020] Figure 1 A flowchart illustrating a method for preparing cold-rolled duplex steel, provided as an embodiment of this application; Figure 2 This is a microstructure diagram of a cold-rolled duplex steel provided in Embodiment 3 of this application. Detailed Implementation
[0021] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only some, not all, of the embodiments of this application. All other embodiments obtained by those skilled in the art based on the embodiments of this application without creative effort are within the scope of protection of this application.
[0022] The range descriptions used in this document, such as numerical ranges and proportional ranges, include all possible sub-ranges and single numerical values within that range. For example, the range descriptions of "1 to 6" or "1~6" cover all sub-ranges between 1 and 6 (such as 1 to 3, 2 to 5, etc.) and single numbers (such as 1, 2, 3, 4, 5, 6). Unless otherwise specified, "content" in this document refers to mass content (mass percentage). Unless otherwise specified, the terms "including," "comprise," etc., used in this document mean "including but not limited to." Relational terms such as "first," "second," etc., are used only to distinguish different entities or operations and do not imply an actual order or relationship. "And / or" indicates that multiple situations can exist individually or simultaneously. Expressions such as "at least one," "multiple," "at least one," etc., refer to any combination of the corresponding objects, including combinations of single or multiple objects. Proportional relationships mentioned in this document, such as mass ratios and molar ratios, should be understood as the correspondence between the first and second terms of a proportional formula, according to the order of description. The raw materials, reagents, instruments, and equipment used in this document can all be obtained through commercial purchase or prepared using existing methods.
[0023] In a first aspect, embodiments of this application provide a cold-rolled dual-phase steel, wherein the chemical composition of the cold-rolled dual-phase steel, by mass fraction, is: C: 0.07%~0.12%, Si: 0%~0.40%, Mn: 1.80%~2.30%, Al: 0.02%~0.06%, Cr: 0.30%~0.60%, Nb: 0.01%~0.04%, Ti: 0.01%~0.04%, P: 0%~0.01%, S: 0%~0.005%, with the remainder being Fe and unavoidable impurities; The positive effects of limiting the C mass fraction to 0.07%~0.12% include: C is an essential solid solution strengthening element that improves the hardenability of cold-rolled duplex steel and promotes martensite formation. However, excessively high C mass fractions can impair the weldability of cold-rolled duplex steel and cause significant segregation. For example, C mass fractions can be 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, etc.
[0024] The positive effects of limiting the Si mass fraction to 0%~0.40% are as follows: Controlling the Si mass fraction below 0.40% can prevent the formation of silicon oxides that are difficult to effectively reduce at grain boundaries during annealing, thereby preventing surface defects and ensuring surface quality. It also helps to ensure the surface plastic deformation capacity of cold-rolled duplex steel during bending. For example, the Si mass fraction can be 0.10%, 0.20%, 0.30%, 0.40%, etc.
[0025] The positive effects of limiting the Mn mass fraction to 1.80%~2.30% include: Mn is a solid solution strengthening element that can expand the austenite region and significantly improve the hardenability of cold-rolled duplex steel. However, excessively high Mn mass fractions can easily cause microstructure segregation, leading to delamination cracking in cold-rolled duplex steel during stamping. For example, the Mn mass fraction can be 1.80%, 1.90%, 2.00%, 2.10%, 2.20%, 2.30%, etc.
[0026] The positive effects of limiting the Al mass fraction to 0.02%~0.06% include: controlling the Al mass fraction within a low range, which can reduce alloy costs while purifying the molten steel through Al's deoxidizing effect. This control method does not excessively increase the ferrite proportion, which is beneficial for maintaining the hardness balance between the ferrite and martensite phases, thereby achieving a coordinated improvement in the bending performance and hole expansion performance of cold-rolled dual-phase steel. For example, the Al mass fraction can be 0.02%, 0.04%, 0.06%, etc.
[0027] The positive effects of limiting the Cr mass fraction to 0.30%~0.60% include: Cr can improve the hardenability of cold-rolled duplex steel, increase austenite stability, and ensure sufficient martensite formation after rapid cooling, thereby guaranteeing the strength of cold-rolled duplex steel. Simultaneously, Cr can inhibit grain growth and refine the microstructure. For example, the Cr mass fraction can be 0.30%, 0.35%, 0.40%, 0.45%, 0.50%, 0.55%, 0.60%, etc.
[0028] The positive effects of limiting the Nb mass fraction to 0.01%~0.04%: Nb is a strong carbonitride forming element, which can significantly refine ferrite grains, thereby improving the strength and toughness of cold-rolled dual-phase steel. For example, the Nb mass fraction can be 0.01%, 0.02%, 0.03%, 0.04%, etc.
[0029] The positive effects of limiting the Ti mass fraction to 0.01%~0.04% include: Ti has nitrogen-fixing properties and can refine grains. The dispersed precipitation of Ti-containing second-phase particles can strengthen ferrite and reduce the hardness difference between ferrite and martensite, thereby improving the hole-expanding and flanging performance of cold-rolled dual-phase steel. For example, the Ti mass fraction can be 0.01%, 0.02%, 0.03%, 0.04%, etc.
[0030] The positive effects of limiting the mass fraction of phosphorus (P) to 0%~0.01% are as follows: Strictly controlling the mass fraction of P to not exceed 0.01% can prevent P segregation at grain boundaries, which can lead to increased brittleness in cold-rolled dual-phase steel. This reduces the risk of cracking along grain boundaries during bending and ensures that the cold-rolled dual-phase steel has good plastic deformation capacity during local forming. For example, the mass fraction of P can be 0.002%, 0.004%, 0.006%, 0.008%, 0.010%, etc.
[0031] The positive effects of limiting the mass fraction of sulfur (S) to 0%~0.005% are as follows: Strictly controlling the mass fraction of S to no more than 0.005% can reduce the formation of sulfide inclusions, preventing these inclusions from becoming stress concentration sources and crack initiation points during bending or hole expansion, thereby improving the overall formability and hole expansion rate of cold-rolled duplex steel. For example, the mass fraction of S can be 0.001%, 0.003%, 0.005%, etc.
[0032] Fe is a matrix element, and the specific content / range of Fe can be obtained through the upper and lower limit formulas of the component, that is: The sum of the percentages of all components in a composition should equal 100%, and the content ranges of several components should meet the following conditions: the upper limit of a certain component + the lower limit of other components ≤ 100; the lower limit of a certain component + the upper limit of other components ≥ 100. Furthermore, the specific content of Fe is made up to 100% by the actual detected values of the other chemical components mentioned above, together with any unlisted active elements and / or impurity elements, and Fe must constitute the absolute proportion as a matrix element.
[0033] The microstructure of the cold-rolled dual-phase steel includes fine and uniform ferrite, diffusely distributed martensite, bainite, and retained austenite. A fine and uniform ferrite matrix helps improve the plasticity and toughness of cold-rolled dual-phase steel, resulting in a more uniform stress distribution during bending and reducing the risk of localized cracking. It also provides a good foundation for strain distribution during the hole-expanding process. Martensite, dispersed in island-like patterns within the ferrite matrix, facilitates uniform strain distribution and reduces the likelihood of localized high strain hardening, thus significantly improving the hole-expanding performance of cold-rolled dual-phase steel. The presence of bainite optimizes the hardness transition between ferrite and martensite, reduces stress concentration at the two-phase interface, and helps balance the conflicting relationship between bending and hole-expanding performance in cold-rolled dual-phase steel. Retained austenite can transform into martensite during forming, generating a transformation-induced plasticity effect, increasing the work hardening rate and uniform elongation of cold-rolled dual-phase steel, thereby enhancing its plastic deformation capacity during bending without compromising hole-expanding performance.
[0034] The thickness of the decarburized layer on the surface of the cold-rolled duplex steel is 5μm~30μm.
[0035] The thickness of the decarburized layer on the surface of cold-rolled duplex steel is controlled between 5 μm and 30 μm. This decarburized layer can increase the volume fraction of ferrite on the surface, significantly improve the elongation of the surface layer of cold-rolled duplex steel, and effectively inhibit the initiation and propagation of cracks during bending, thereby improving the bending performance of cold-rolled duplex steel. For example, the thickness of the decarburized layer on the surface of cold-rolled duplex steel can be 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, etc.
[0036] In some embodiments, the cold-rolled duplex steel can be used for forming automotive structural components.
[0037] In some embodiments, the volume fraction of ferrite is 43% to 55%, and the volume fraction of martensite is 35% to 55%.
[0038] The ferrite volume fraction, controlled between 43% and 55%, provides sufficient plasticity and elongation for cold-rolled dual-phase steel, effectively dispersing stress and inhibiting crack initiation during bending, while also providing a good deformation basis for strain distribution during hole expansion. The martensite volume fraction, controlled between 35% and 55%, provides sufficient tensile strength for cold-rolled dual-phase steel, while maintaining a dispersed island-like distribution. This avoids the reduction in microstructure uniformity due to excessive martensite volume fraction leading to lath martensite dominance, thus ensuring that the bending performance of cold-rolled dual-phase steel is not compromised while maintaining its hole expansion performance. For example, the ferrite volume fraction can be 43%, 46%, 49%, 52%, 55%, etc.; the martensite volume fraction can be 35%, 40%, 45%, 50%, 55%, etc.
[0039] In some embodiments, the cold-rolled duplex steel meets the following properties: yield strength of 435 MPa to 535 MPa, tensile strength of 780 MPa to 900 MPa, and longitudinal elongation A. 80 ≥19%, with an expansion rate of 35%~45%, and no cracking when bending at 90° laterally with a bending mandrel radius of 0.5mm.
[0040] Yield strength: The yield limit of a metallic material when it yields, i.e., the stress value at which the material resists a small amount of plastic deformation. The yield strength is controlled between 435 MPa and 535 MPa to ensure that cold-rolled duplex steel has sufficient resistance to deformation under external forces, meeting structural load-bearing requirements while avoiding a decrease in plasticity due to excessive strength, thus ensuring that the cold-rolled duplex steel does not suffer permanent failure during the forming process of complex parts. For example, the yield strength can be 435 MPa, 485 MPa, 535 MPa, etc. Tensile strength: The maximum tensile stress that a material can withstand during tension, indicating the maximum load the material can withstand before fracture. The tensile strength is controlled between 780 MPa and 900 MPa to ensure that the cold-rolled duplex steel has sufficient strength reserve during service, capable of withstanding high working loads without fracture, while maintaining a reasonable yield-to-strength ratio with the yield strength, balancing the strength and formability of the cold-rolled duplex steel, and meeting the requirements of high strength and good plasticity matching for automotive cold-rolled duplex steel. For example, tensile strength can be 780 MPa, 820 MPa, 860 MPa, 900 MPa, etc. Elongation: One of the indicators describing the plastic properties of a material, referring to the percentage of the total deformation of the gauge length after tensile fracture of the specimen to the original gauge length. A 80 This represents the elongation after fracture measured using a non-proportional specimen with an initial gauge length of 80 mm. Longitudinal elongation A 80≥19% ensures that cold-rolled duplex steel has sufficient overall plastic deformation capacity, enabling it to fully disperse tensile stress during bending and preventing localized fracture due to insufficient plasticity, thus providing a fundamental guarantee for bending performance. For example, longitudinal elongation A... 80 The expansion ratio can be 19%, 20%, 21%, 22%, etc. Hole expansion ratio: a key indicator for evaluating the edge forming performance of steel plates, reflecting the material's ability to resist cracking at the edge after shearing or punching. Controlling the hole expansion ratio between 35% and 45% ensures that cold-rolled duplex steel has sufficient crack resistance when subjected to local deformation at the sheared edge, reducing the risk of edge crack initiation and propagation during hole expansion, thus meeting the application requirements of automotive parts for high hole expansion forming performance. For example, the expansion ratio can be 35%, 40%, 45%, etc. A 90° transverse bend with a bending mandrel radius of 0.5mm without cracking verifies that cold-rolled duplex steel can maintain the integrity of the surface and the bent part even under extremely small bending mandrel radii, proving that cold-rolled duplex steel achieves a good balance between surface plastic deformation capacity and internal microstructure uniformity, effectively supporting both bending performance and hole expansion performance.
[0041] Figure 1 This is a flowchart illustrating a method for preparing cold-rolled duplex steel, as provided in an embodiment of this application.
[0042] Please see Figure 1 Secondly, this application provides a method for preparing the cold-rolled duplex steel described in the first aspect, the method comprising: S1. Molten steel with the following chemical composition is subjected to ladle refining and vacuum circulation degassing treatment in sequence. The molten steel after vacuum circulation degassing treatment is continuously cast to obtain a slab: C: 0.07%~0.12%, Si: 0%~0.40%, Mn: 1.80%~2.30%, Al: 0.02%~0.06%, Cr: 0.30%~0.60%, Nb: 0.01%~0.04%, Ti: 0.01%~0.04%, P: 0%~0.01%, S: 0%~0.005%, with the remainder being Fe and unavoidable impurities; S2. The slab is sequentially heated, rough-rolled, finish-rolled, and coiled to obtain a hot-rolled coil; S3. The hot-rolled coil is sequentially pickled and cold-rolled in multiple passes to obtain a cold-hardened coil; S4. The cold-rolled coil is subjected to continuous annealing and finishing in sequence to obtain cold-rolled dual-phase steel.
[0043] In some embodiments, the heating temperature is 1200℃~1280℃, the heating time in the furnace is 180min~260min, and the heating soaking time is ≥35min.
[0044] The heating temperature is controlled between 1200℃ and 1280℃ to ensure full austenitization of the slab during heating, while avoiding excessively high temperatures that could lead to grain coarsening or overheating. This provides a uniform microstructure for subsequent rolling, which is beneficial for the formation of fine, uniform ferrite and dispersed island-like martensite in the final cold-rolled dual-phase steel, balancing bending performance and hole-expanding properties. Examples of heating temperatures include 1200℃, 1220℃, 1240℃, 1260℃, and 1280℃. The furnace time is controlled between 180min and 260min to ensure uniform overall temperature and thorough heating of the slab, eliminating internal defects in the ingot and improving microstructure uniformity. This avoids inherited defects due to insufficient heating time or abnormal grain growth due to excessive heating time, thus ensuring a uniform and fine microstructure. Examples of furnace times include 180min, 200min, 220min, 240min, and 260min. The soaking time during heating should be ≥35 min to ensure that the slab is fully homogenized within the highest temperature range, allowing for uniform diffusion of alloying elements and eliminating compositional segregation. This creates conditions for the uniform distribution of alloying elements and precise control of the two-phase ratio in subsequent microstructure regulation, which is beneficial for coordinating the bending and expansion properties of cold-rolled dual-phase steel. For example, the soaking time can be 35 min, 40 min, 45 min, etc.
[0045] In some embodiments, the finishing rolling temperature is ≥880°C.
[0046] The finishing rolling temperature is ≥880℃ to ensure that the rolling process is completed in the austenitic region, avoiding uneven microstructure caused by rolling in the two-phase region at excessively low temperatures. This ensures the uniformity of the microstructure and grain refinement of the hot-rolled coil, laying a good foundation for obtaining a fine and uniform two-phase microstructure through subsequent cold rolling annealing. For example, the finishing rolling temperature can be 880℃, 900℃, 920℃, etc.
[0047] In some embodiments, the winding temperature is 500°C to 600°C.
[0048] The coiling temperature is controlled between 500℃ and 600℃ to ensure a reasonable ratio of ferrite to pearlite in the hot-rolled microstructure. This avoids excessive pearlite content or over-hardening due to excessively low coiling temperatures, providing a suitable initial microstructure for subsequent cold rolling annealing. Ultimately, this contributes to a balance between the bending and expansion properties of the cold-rolled dual-phase steel. For example, the coiling temperature can be 500℃, 550℃, or 600℃.
[0049] In some embodiments, the total reduction rate of the multi-pass cold rolling is 45% to 70%.
[0050] The total reduction rate of multi-pass cold rolling is controlled between 45% and 70% to ensure sufficient deformation during the cold rolling process to break up carbides in the hot-rolled microstructure and refine the grains. This provides sufficient deformation energy for ferrite recrystallization and uniform martensite nucleation during subsequent annealing. Simultaneously, it avoids insufficient microstructure refinement due to an excessively low total reduction rate or exacerbated edge waviness defects due to an excessively high total reduction rate. This is beneficial for obtaining a fine and uniform dual-phase microstructure and coordinately improving the bending and expansion properties of cold-rolled dual-phase steel. For example, the total reduction rate of multi-pass cold rolling can be 45%, 50%, 55%, 60%, 65%, 70%, etc.
[0051] In some embodiments, the continuous annealing rate is 90 m / min to 180 m / min.
[0052] The continuous annealing speed is controlled between 90 m / min and 180 m / min. Precise control of the residence time of the cold-rolled duplex steel in each temperature zone of the annealing furnace allows for sufficient recrystallization of ferrite, forming a fine and uniform matrix structure. Simultaneously, it ensures that martensite precipitates in a dispersed island-like morphology during the subsequent rapid cooling process. This avoids grain coarsening due to excessively slow annealing speed and over-tempering in the over-aging section, or insufficient austenitization in the heating section and insufficient tempering in the over-aging section due to excessively fast annealing speed. Therefore, the bending properties of the cold-rolled duplex steel are improved while maintaining its expansion performance. For example, the continuous annealing speed can be 90 m / min, 135 m / min, 180 m / min, etc.
[0053] In some embodiments, the continuous annealing includes a heating stage, a heating stage, a soaking stage, a slow cooling stage, a rapid cooling stage, an aging stage, and an aging stage. The temperature of the first heating stage is 400℃~550℃, and the heating rate of the first heating stage is 0.7℃ / s~2.4℃ / s; the temperature of the second heating stage is 780℃~840℃, and the heating rate of the second heating stage is 1.5℃ / s~5.4℃ / s; the temperature of the soaking stage is 780℃~840℃; the temperature of the slow cooling stage is 600℃~680℃; the temperature of the rapid cooling stage is 270℃~350℃, and the rapid cooling rate of the rapid cooling stage is 20℃ / s~60℃ / s; the temperature of the first aging stage is 270℃~350℃; the temperature of the second aging stage is 300℃~400℃, and the temperature of the second aging stage is 20℃~50℃ higher than the temperature of the first aging stage.
[0054] The temperature of the first heating stage is controlled between 400℃ and 550℃, and the heating rate is controlled between 0.7℃ / s and 2.4℃ / s. This temperature and rate control allows the cold-rolled duplex steel to heat up slowly in the lower temperature range, fully releasing the work hardening stress from the cold rolling process and activating ferrite recrystallization nucleation. Simultaneously, this control method avoids excessively rapid heating that could lead to stress concentration or abnormal grain growth, thus providing a uniform and fine initial recrystallization structure for the subsequent high-temperature heating stage. For example, the temperature of the first heating stage can be 400℃, 450℃, 500℃, 550℃, etc.; and the heating rate can be 0.7℃ / s, 1.4℃ / s, 2.1℃ / s, etc.
[0055] The temperature of the second heating stage is controlled between 780℃ and 840℃. This temperature range ensures an appropriate austenite volume fraction, avoiding insufficient austenitization due to excessively low temperatures or grain coarsening due to excessively high temperatures. Simultaneously, the heating rate of the second stage is controlled between 1.5℃ / s and 5.4℃ / s. This rate range increases the austenite nucleation rate during heating, resulting in a fine austenite structure, which then transforms into a fine and uniform martensite structure after cooling, thereby improving the strength and overall performance of the cold-rolled duplex steel. For example, the temperature of the second heating stage can be 780℃, 800℃, 820℃, 840℃, etc.; and the heating rate can be 1.5℃ / s, 2.5℃ / s, 3.5℃ / s, 4.5℃ / s, etc.
[0056] The temperature of the soaking zone is controlled between 780℃ and 840℃ to ensure sufficient heat preservation of the cold-rolled duplex steel. Sufficient heat preservation ensures homogenization of the austenite composition, promotes full diffusion of alloying elements, and stabilizes the ratio of ferrite to austenite. This temperature and heat preservation control lays the compositional and microstructural foundation for obtaining a dispersed martensite structure in the subsequent cooling stage. For example, the temperature of the soaking zone can be 780℃, 800℃, 820℃, 840℃, etc.
[0057] The temperature of the slow cooling section is controlled between 600℃ and 680℃, allowing the cold-rolled duplex steel to cool at a suitable rate in the two-phase region. This cooling process promotes the preferential nucleation and growth of ferrite along austenite grain boundaries, thereby further regulating the volume fraction and grain size of ferrite. This temperature control method avoids the introduction of unwanted phases such as bainite into the microstructure due to excessively low temperatures in the slow cooling section, preventing these unwanted phases from impairing the uniformity of the mechanical properties of the cold-rolled duplex steel. For example, the temperature of the slow cooling section can be 600℃, 640℃, 680℃, etc.
[0058] The temperature of the rapid cooling section is controlled between 270℃ and 350℃, and the cooling rate is controlled between 20℃ / s and 60℃ / s. This temperature and rate control allows the untransformed austenite in the cold-rolled dual-phase steel to rapidly cross the pearlite and bainite transformation zones, directly quenching to form martensite, thereby ensuring the achievement of the target proportion of martensite phase. For example, the temperature of the rapid cooling section can be 270℃, 310℃, 350℃, etc.; the cooling rate can be 20℃ / s, 30℃ / s, 40℃ / s, 50℃ / s, 60℃ / s, etc.
[0059] The aging temperature is controlled between 270℃ and 350℃. This temperature control ensures that the microstructure remains stable under constant temperature conditions after the martensitic transformation is basically completed, preventing the continued decomposition of incompletely transformed residual austenite due to temperature fluctuations. For example, the aging temperature can be 270℃, 310℃, 350℃, etc.
[0060] The temperature of the second aging stage is controlled at 300℃~400℃, and the temperature of the second aging stage is 20℃~50℃ higher than that of the first aging stage. This temperature control enables online tempering, causing fine carbides to precipitate in the lath martensite and forming a certain amount of tempered martensite, thereby reducing the hardness difference between the soft phase ferrite and the hard phase martensite, and significantly improving the porosity of cold-rolled dual-phase steel. Simultaneously, this temperature control avoids insufficient improvement in hardness difference due to excessively low temperatures, or excessive decomposition of martensite due to excessively high temperatures, which would damage strength. For example, the temperature of the second aging stage can be 300℃, 350℃, or 400℃; the temperature of the second aging stage can be 20℃, 30℃, 40℃, or 50℃ higher than that of the first aging stage, etc.
[0061] In some embodiments, the cold-rolled coil is subjected to segmented humidification during the continuous annealing process, and the flow rate of the segmented humidification process is 5 kg / h to 20 kg / h; the segmented humidification process is carried out in the first heating stage and / or the second heating stage temperature zone.
[0062] In the continuous annealing process, the cold-rolled coils undergo segmented humidification treatment with a flow rate of 5 kg / h to 20 kg / h. This segmented humidification is carried out in the first and / or second heating zones. This humidification flow rate maintains a specific oxidation potential within the furnace atmosphere, precisely controlling the reaction degree between carbon atoms on the surface of the cold-rolled duplex steel and oxygen and water vapor in the atmosphere, thereby forming a decarburized layer with a thickness of 5 μm to 30 μm on the surface of the cold-rolled duplex steel. The significantly increased proportion of surface ferrite in this decarburized layer improves the elongation of the surface layer of the cold-rolled duplex steel, thus enhancing its resistance to crack initiation and propagation during bending. Simultaneously, this flow rate control avoids insufficient decarburization due to excessively low humidification flow rate, or excessively high humidification flow rate leading to excessive decarburization and severe surface oxidation, which would impair the hole-expanding performance. Therefore, the bending and hole-expanding performance of the cold-rolled duplex steel are ultimately synergistically optimized. For example, the flow rate of segmented humidification can be 5 kg / h, 10 kg / h, 15 kg / h, 20 kg / h, etc.
[0063] The product obtained by this cold-rolled duplex steel preparation method is the aforementioned cold-rolled duplex steel. Since the cold-rolled duplex steel preparation method adopts some or all of the technical solutions of the cold-rolled duplex steel embodiments, it has at least all the beneficial effects brought about by the technical solutions of the aforementioned embodiments, which will not be elaborated here.
[0064] The present application is further illustrated below with reference to specific embodiments. Experimental methods in the following embodiments that do not specify specific conditions are generally determined according to national standards / industry standards / the disclosure herein; if there are no corresponding national standards / industry standards / the disclosure herein, they are performed according to generally accepted international standards, conventional conditions, or conditions recommended by the manufacturer.
[0065] The chemical composition (mass percentage) of the examples and comparative examples is shown in Table 1.
[0066] Table 1
[0067] Based on the chemical composition of the embodiments and comparative examples, this embodiment also provides a method for preparing cold-rolled duplex steel, including the following steps: The molten steel with the chemical composition described in Table 1 was subjected to ladle refining and vacuum circulation degassing treatment in sequence. The molten steel after vacuum circulation degassing treatment was then continuously cast to obtain a slab. The slab is heated, rough rolled, finish rolled and coiled in sequence to obtain a hot-rolled coil; Hot-rolled coils are pickled and cold-rolled in multiple passes to obtain cold-hardened coils. The cold-rolled coils were sequentially annealed and finished to obtain cold-rolled dual-phase steel. Please refer to Tables 2 and 3 for the process parameters.
[0068] The process parameters for the examples and comparative examples are shown in Tables 2 and 3.
[0069] Table 2
[0070] Table 3
[0071] The performance of the examples and comparative examples is shown in Table 4.
[0072] Table 4
[0073] The data tables above provide a clear comparison of the differences between various embodiments and comparative examples. The following conclusions can be drawn: As can be seen from the data in Table 4, the cold-rolled duplex steel provided in this application embodiment has a yield strength of 435MPa~477MPa, a tensile strength of 788MPa~815MPa, and a longitudinal elongation A. 80 The carbon content is 20.0%~22.5%, the decarburized layer thickness is 6μm~15μm, the porosity is 35.5%~40.5%, and it does not crack when bent at a 90° angle with a bending mandrel radius of 0.5mm in the transverse direction, with good surface quality.
[0074] As can be seen from Examples 1-3 and Comparative Examples 1-3, Examples 1-3 successfully achieved excellent comprehensive mechanical properties by controlling the key chemical components within a reasonable range and coordinating with optimized hot rolling and continuous annealing processes. However, Comparative Example 1, due to a slightly higher coiling temperature and the lack of segmented humidification, had a decarburized layer thickness of only 3 μm, resulting in micro-cracks during bending and a porosity of only 28.0%. Comparative Example 2, due to excessively high flow rate (30 kg / h) during segmented humidification, resulted in surface blackening, and the high coiling temperature (645°C) led to a relatively coarse initial microstructure; even with humidification, the bending performance could not be fundamentally improved, and the porosity decreased to 29.5%. Comparative Example 3, due to the lack of segmented humidification, excessively high coiling temperature (675°C), and high carbon and manganese mass fractions (0.12% and 2.30%, respectively), resulted in a longitudinal elongation of only 16.5%, bending cracks, and a porosity of only 30.0%. In summary, the synergistic effect of reasonable chemical composition, heating temperature, winding temperature, segmented humidification flow rate, rapid cooling parameters, and time-stage aging control are key factors for obtaining excellent bending and hole-expanding performance, and none of them can be omitted.
[0075] Appendix Figure 2 Detailed explanation: Figure 2 This is a microstructure diagram of a cold-rolled dual-phase steel provided in Embodiment 3 of this application. According to... Figure 2It can be determined that the dark gray matrix is ferrite, and the bright white island-like precipitates are martensite. The martensite phase is uniformly and diffusely distributed in the ferrite matrix, and the martensite is small and uniform in size, resulting in good overall microstructure homogeneity. This ideal dual-phase microstructure directly corresponds to the excellent comprehensive mechanical properties of cold-rolled dual-phase steel.
[0076] One or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages: This invention provides a cold-rolled duplex steel. By controlling key chemical components within a reasonable range and coordinating optimized hot rolling, cold rolling, and continuous annealing process parameters, a cold-rolled duplex steel for automotive applications with excellent bending and hole-expanding properties was successfully prepared. Specifically, this solution involves precise control of heating temperature, coiling temperature, segmented humidification flow rate, rapid cooling section temperature and cooling rate, and aging section temperature gradient. Ultimately, this results in a cold-rolled duplex steel exhibiting high longitudinal elongation, no cracking during transverse bending, good hole expansion rate, and excellent surface quality. With its superior bending and hole-expanding capabilities, this cold-rolled duplex steel can meet the deformation requirements of complex parts, effectively improving the compatibility between the cold-rolled duplex steel and different dies, significantly reducing the break-in period between the cold-rolled duplex steel and the dies, thereby lowering production preparation costs. Furthermore, this technical solution employs a low-cost alloy composition design, offering significant cost advantages while ensuring mechanical properties meet standards, and possesses promising prospects for industrial application.
[0077] The above description is merely a specific embodiment of this application, enabling those skilled in the art to understand or implement this application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of this application. Therefore, this application is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features claimed in this application.
Claims
1. A cold-rolled dual-phase steel, characterized in that, The chemical composition of the cold-rolled dual-phase steel, by mass fraction, is as follows: C: 0.07%~0.12%, Si: 0%~0.40%, Mn: 1.80%~2.30%, Al: 0.02%~0.06%, Cr: 0.30%~0.60%, Nb: 0.01%~0.04%, Ti: 0.01%~0.04%, P: 0%~0.01%, S: 0%~0.005%, with the remainder being Fe and unavoidable impurities; The microstructure of the cold-rolled dual-phase steel includes fine and uniform ferrite, diffusely distributed martensite, bainite, and retained austenite. The thickness of the decarburized layer on the surface of the cold-rolled duplex steel is 5μm~30μm.
2. The cold-rolled duplex steel according to claim 1, characterized in that, The volume fraction of ferrite is 43% to 55%, and the volume fraction of martensite is 35% to 55%.
3. The cold-rolled duplex steel according to claim 1, characterized in that, The cold-rolled duplex steel meets the following properties: yield strength of 435MPa~535MPa, tensile strength of 780MPa~900MPa, and longitudinal elongation A. 80 ≥19%, with an expansion rate of 35%~45%, and no cracking when bending at 90° laterally with a bending mandrel radius of 0.5mm.
4. A method for preparing cold-rolled duplex steel according to any one of claims 1 to 3, characterized in that, The method includes: Molten steel having the chemical composition described in any one of claims 1 to 3 is subjected to ladle refining and vacuum circulation degassing in sequence, and the molten steel after vacuum circulation degassing is continuously cast to obtain a slab. The slab is sequentially heated, rough-rolled, finish-rolled, and coiled to obtain a hot-rolled coil. The hot-rolled coil is sequentially pickled and cold-rolled in multiple passes to obtain a cold-hardened coil. The cold-rolled coil is subjected to continuous annealing and finishing to obtain cold-rolled dual-phase steel.
5. The method according to claim 4, characterized in that, The heating temperature is 1200℃~1280℃, the heating time in the furnace is 180min~260min, and the heating soaking time is ≥35min.
6. The method according to claim 4, characterized in that, The finishing rolling temperature is ≥880℃; and / or, The winding temperature is 500℃~600℃.
7. The method according to claim 4, characterized in that, The total reduction rate of the multi-pass cold rolling is 45% to 70%.
8. The method according to claim 4, characterized in that, The continuous annealing speed is 90 m / min to 180 m / min.
9. The method according to claim 4, characterized in that, The continuous annealing includes a heating stage, a heating stage, a soaking stage, a slow cooling stage, a rapid cooling stage, an aging stage, and an aging stage. The temperature of the heating section is 400℃~550℃, and the heating rate of the heating section is 0.7℃ / s~2.4℃ / s; The temperature of the second heating section is 780℃~840℃, and the heating rate of the second heating section is 1.5℃ / s~5.4℃ / s; The temperature of the heat spreader is 780℃~840℃; The temperature of the slow cooling section is 600℃~680℃; The temperature of the rapid cooling section is 270℃~350℃, and the rate of the rapid cooling section is 20℃ / s~60℃ / s; The temperature for the first aging stage is 270℃~350℃; The temperature of the second aging stage is 300℃~400℃, and the temperature of the second aging stage is 20℃~50℃ higher than the temperature of the first aging stage.
10. The method according to claim 9, characterized in that, During the continuous annealing process, the cold-hardened roll is subjected to segmented humidification treatment, and the flow rate of the segmented humidification treatment is 5 kg / h to 20 kg / h; the segmented humidification treatment is carried out in the first heating stage and / or the second heating stage temperature zone.